2019
DOI: 10.2147/rrtm.s201159
|View full text |Cite
|
Sign up to set email alerts
|

<p>Epilepsy diagnosis and management of children in Kenya: review of current literature</p>

Abstract: Introduction: The growing impact of non-communicable diseases in low- to middle-income countries makes epilepsy a key research priority. We evaluated peer-reviewed published literature on childhood epilepsy specific to Kenya to identify knowledge gaps and inform future priorities. Methodology: A literature search utilizing the terms “epilepsy” OR “seizure” as exploded subject headings AND “Kenya” was conducted. Relevant databases were searched, generating 908 articles. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Co-morbidity or history of infectious diseases affecting more than 10%, was similar for both genders and in line or slightly lower (range 5.5%-13%) than in other SSA regions (Assadeck et al, 2019;Bistervels et al, 2016;Burton et al, 2012;Carter et al, 2004;Kariuki et al, 2014;Samia et al, 2019). The frequency of cerebral malaria in our cohort of PwE was higher than the reported malaria prevalence of 1% in the There is a clear association between epilepsy and HIV with newonset seizures occurring in up to 11% of HIV infected persons (Howlett, 2019).…”
Section: Epilepsy Characteristics and Gender Specificssupporting
confidence: 64%
“…Co-morbidity or history of infectious diseases affecting more than 10%, was similar for both genders and in line or slightly lower (range 5.5%-13%) than in other SSA regions (Assadeck et al, 2019;Bistervels et al, 2016;Burton et al, 2012;Carter et al, 2004;Kariuki et al, 2014;Samia et al, 2019). The frequency of cerebral malaria in our cohort of PwE was higher than the reported malaria prevalence of 1% in the There is a clear association between epilepsy and HIV with newonset seizures occurring in up to 11% of HIV infected persons (Howlett, 2019).…”
Section: Epilepsy Characteristics and Gender Specificssupporting
confidence: 64%
“…The etiology of seizures and epilepsy in childhood in these areas follows a different pattern where acquired causes (eg, perinatal and neonatal adverse events, infections) represent the principal causes. 16…”
Section: Key Pointsmentioning
confidence: 99%
“…A multicenter study conducted in Kenya, South Africa, Uganda, Tanzania, and Ghana in a total of 1711 individuals with active convulsive epilepsy found an odds ratio of 1.39 with previous exposure to T. gondii [74]. Moreover, studies from Kenya and other African countries concluded that in addition to Toxoplasma infection, malaria, onchocerciasis, neurocysticercosis, and toxocariasis also might be involved in the pathogenesis of epilepsy [75,76]. There is also evidence of possible association with some neurodegenerative disorders, such as Parkinson and Alzheimer diseases, in which the prevalence of Toxoplasma infection is around 85% and 66%, respectively [3,[77][78][79][80][81].…”
Section: Toxoplasma Infection In Immunocompetent Patientsmentioning
confidence: 99%